Rick and Morty. Volume twelve - Starks, Kyle (Oni Press Inc., 2021)
Tired of forever being in danger, Morty gets Rick to procure him a powerful armored suit, but of course things never go easy like you'd expect, bruh. Read now the tale of THE RICKONING, an event so cataclysmic that the worlds of Rick and Morty will never be the same. Collecting issues #56-60 of the hit series from Oni Press, this is a must-read for any and all fans of Cartoon Network's Rick and Morty.